PELAKSANAAN PELINDUNGAN ADMINISTRATIF DAN TEKNIS PEKERJA MIGRAN INDONESIA (PMI) KE LUAR NEGERI (Studi Pada Dinas Ketenagakerjaan Kota Bengkulu) - Juliska, Sanggera; Djonet Santoso; Yorry Hardayani (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
The purpose of this study is to know, describe and understand in depth related to the causes of the non-optimal implementation of administrative and technical protection of migrant workers abroad at the Bengkulu City Manpower Office. To determine the achievement of these goals, this study uses the theory of policy implementation by Riant Nugroho (2017), namely at the implementation stage and guided by Government Regulation of the Republic of Indonesia Number 59 of 2021 concerning the Implementation of PMI Protection, the aspects of this study are: administrative protection and technical protection. The method used in this study is descriptive qualitative. The data collection uses observation, interview, and documentation methods. The results of this study show that the implementation of administrative and technical protection of migrant workers abroad at the Bengkulu City Manpower Office has not been carried out optimally because the technical protection aspect has experienced obstacles where socialization is fully handed over to P3MI, making it difficult for the community to distinguish between legal and safe P3MI. Then the establishment of LTSA, placement and protection of PMI in Bengkulu City has not been carried out.